IMPLEMENTASI PEMBIASAAN KARAKTER DISIPLIN MELALUI ANALISA KONSEP HABITUS DAN ARENA PIERRE BOURDIEU PADA SISWA SEKOLAH DASAR - Anjarwati, Dwi; Kusumawati, Dian; Muslim, Rachmat Imam (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2026)
This study aims to analyze the implementation of habituation of discipline character in grade V students of SDN Kalisari through the concept of habitus and arena Pierre Bourdieu. A qualitative approach with phenomenological design is used to delve deeply into the experiences of principals, teachers, and students towards the habituation practices that take place. Data was collected through observation, interviews, and documentation, then analyzed inductively based on the Miles and Huberman steps. The results of the study showed that routinely habitual practices such as morning prayers, Asmaul Husna readings, dhuha and dzuhur prayers, flag ceremonies, gymnastics, and class pickets succeeded in forming an automatic pattern of disciplined behavior. This process occurs through the gradual internalization of values so that the discipline evolves from external obedience to internal awareness. The difference in the level of discipline between students is influenced by variations in initial habitus, especially family support and home environment. Habituation has proven to be more effective than the reward-punishment approach because it is able to instill values, strengthen self-regulation, and reproduce cultural capital through the example of teachers and the structure of school activities. The novelty of this research lies in the use of Pierre Bourdieu's concept of habitus and arena as an analytical framework to explain the process of internalizing the character of discipline through habituation in elementary schools which has been studied more normatively and descriptively.